Canine hepacivirus is not associated with chronic liver disease in dogs - Bexfield, N. H. (Blackwell Scientific Publications, 2013)
Canine hepacivirus (CHV) has recently been identified in liver and respiratory tract samples from dogs, and comparative phylogenetic analysis has confirmed it to be the closest genetic relative of hepatitis C virus (HCV) described to date. CHV offers great potential as a model system for HCV, but only if the underlying processes of infection and pathogenesis are similar for both viruses. However, it is not yet clear if CHV is hepatotrophic. Canine chronic hepatitis (CH) is a common and usually idiopathic disease that shares similar histological features to that of HCV infection of humans. To date, no study has attempted to determine whether CHV is involved in the aetiology of liver disease in dogs. We employed two nested PCR assays, using primers targeting regions of the helicase domain of CHV NS3, to identify viral nucleic acids in liver samples from 100 dogs with CH of unknown cause in the UK. We also used a sensitive luciferase immunoprecipitation system (LIPS) assay to screen serum samples from these dogs for the presence of anti‐CHV antibodies. Surprisingly, there was no evidence of exposure to, or a carrier state of, CHV in this large cohort, suggesting that the virus is not associated with CH in UK dogs. Future work, including transmission studies, is required to understand the pathogenesis of CHV in canids before it can be proposed as a surrogate model for HCV‐induced liver disease in man.